Corporate governance challenges in initial coin offerings - REMOLINA LEON, Nydia (Institutional Knowledge at Singapore Management University, 2021)
Initial Coin Offerings (ICOs) have become an important fundraising method for firms. While most regulators, academics and policymakers have focused their attention on whether and, if so, when ICOs are subject to securities laws, they have overlooked other legal issues involved in an ICO. This article seeks to partially fill this gap by analysing the corporate governance challenges of ICOs. Namely, it will explore the exacerbated agency problems existing between the issuers and buyers of tokens, and why traditional corporate governance mechanisms fail to protect tokenholders. Based on a functional and comparative analysis of ICOs, with particular emphasis on the regulatory responses generally provided in Asia, Europe, the United Kingdom, and the United States, this chapter highlights the corporate governance problems arising in ICOs. It also suggests various policy recommendations to improve the attractiveness of ICOs as a fundraising method while reducing the risk of opportunism of promoters vis-à-vis tokenholders.